A Healthier Lifestyle Pattern for Cardiovascular Risk Reduction Is Associated With Better Bone Mass in Southern Chinese Elderly Men and Women. Issue 31 (August 2015) - Liu, Zhao-min; Wong, Carmen Ka Man; Wong, Samuel Yeung-shan; Leung, Jason; Tse, Lap Ah; Chan, Ruth; Woo, Jean; Leonard, Anang Sowah.
<x xml:space="preserve">Abstract</x> Abstract Lifestyle factors have been linked to bone health, however little is known about their combined impact on bone. Cardiovascular disease (CVD) and osteoporosis are 2 major public health problems that share some common pathophysiology. We aimed to assess whether higher adherence to American Heart Association diet and lifestyle recommendations (AHA-DLR) was associated with better bone health in Chinese elderly. This was a cross-sectional study using data from the largest population-based study on osteoporosis in Asia (Mr and Ms Os, Hong Kong). The study recruited 4000 independent walking Chinese men and women aged ≥65 year. Information on demographic, health, and lifestyle factors was obtained by standardized questionnaires. An overall lifestyle score was estimated based on a modified adherence index of AHA-DLR. Bone mineral measurements of the whole body, total hip, lumbar spine, and femoral neck were made by dual-energy X-ray absorptiometry. Most lifestyle factors alone were not significantly associated bone mass. Overall lifestyle score in the highest quartile compared with the lowest quartile had significantly better bone mass at all sites in a dose–response manner. Every 10-unit of lifestyle score increase was associated with 0.005, 0.004, and 0.007 g/cm2 increases of bone mineral density (BMD) at whole body, femur neck, and total hip, respectively (all P < 0.05), and 13.2% (odds ratio 0.868; 95% CI 0.784, 0.961) decreased risk of osteoporosis at total hip after adjustment for potential covariates. Our study suggested that greater adherence to an overall healthy lifestyle for CVD risk reduction was associated with better bone mass among Chinese elderly.